Dispute Resolution of Collateral Sale in Murabahah Contract - Agi Attaubah Hidayat; Omar Khalid Bhatti; Hasan Bisri; Cucu Susilawati (Indonesian Journal of Law and Islamic Law (IJLIL), 2025)
This study analyzes Case No. 5/Pdt.GS/2021/PA.Sbg, addressing a contentious issue concerning the sale of collateral by the debtor. The sale of collateral occurred without the acknowledgment of the plaintiff’s claims regarding the seizure of the collateral and the establishment of auction rights. This research investigates the dispute surrounding a default under a Murabahah contract as discussed in the decision rendered by the Subang Religious Court (Case No. 5/Pdt.GS/2021/PA.Sbg). Furthermore, the study examines the application of Sharia economic law in resolving collateral ownership transfers, as outlined in the court’s decision. A normative legal methodology is employed, incorporating case law, statutory provisions, and conceptual analysis. The findings are as follows: first, the plaintiff’s lawsuit in Case No. 5/Pdt.GS/2021/PA.Sbg centered on the defendant's default in settling the financing agreement within the stipulated timeframe and the subsequent discovery of collateral sale. Second, the legal reasoning in Decision No. 5/Pdt.GS/2021/PA.Sbg is based on Islamic principles (Al-Qur'an), Fiqh rules, the Civil Code (KUH Perdata), the Civil Procedure Law (HIR), Law No. 4 of 1996 concerning Mortgage Rights, and Law No. 37 of 2004 regarding Bankruptcy and Suspension of Debt Payment Obligations. Finally, the settlement of the case demonstrates the court's adherence to the principle of justice by granting the defendant an extension to fulfill the contract, in alignment with Q.S. Al-Baqarah verse 280. However, the case resolution did not fully apply the principles of justice, utility, and legal certainty in a balanced manner. This study analyzes Case No. 5/Pdt.GS/2021/PA.Sbg, addressing a contentious issue concerning the sale of collateral by the debtor. The sale of collateral occurred without the acknowledgment of the plaintiff’s claims regarding the seizure of the collateral and the establishment of auction rights. This research investigates the dispute surrounding a default under a Murabahah contract as discussed in the decision rendered by the Subang Religious Court (Case No. 5/Pdt.GS/2021/PA.Sbg). Furthermore, the study examines the application of Sharia economic law in resolving collateral ownership transfers, as outlined in the court’s decision. A normative legal methodology is employed, incorporating case law, statutory provisions, and conceptual analysis. The findings are as follows: first, the plaintiff’s lawsuit in Case No. 5/Pdt.GS/2021/PA.Sbg centered on the defendant's default in settling the financing agreement within the stipulated timeframe and the subsequent discovery of collateral sale. Second, the legal reasoning in Decision No. 5/Pdt.GS/2021/PA.Sbg is based on Islamic principles (Al-Qur'an), Fiqh rules, the Civil Code (KUH Perdata), the Civil Procedure Law (HIR), Law No. 4 of 1996 concerning Mortgage Rights, and Law No. 37 of 2004 regarding Bankruptcy and Suspension of Debt Payment Obligations. Finally, the settlement of the case demonstrates the court's adherence to the principle of justice by granting the defendant an extension to fulfill the contract, in alignment with Q.S. Al-Baqarah verse 280. However, the case resolution did not fully apply the principles of justice, utility, and legal certainty in a balanced manner.